Aplikasi PLC Menggunakan Mikrokontroler PIC 16F877A - Purnama Irwan (Jurnal Sains dan Ilmu Terapan, 2018)
In this study, the use of the PLC application with the PIC 16F877A microcontroller is described, starting from circuit design, assembly, and its use in several applications in PLCs including: setting railroad crossings, distributing goods on conveyors, and setting traffic lights. Programming the ladder diagram of the application is done with the LDmicro program. From the results of this study it is hoped that a PLC device that is more economical, has high reliability and is easy to operate can be made.